Characteristics of Ultrasonic Wave Propagation in Reinforced Concrete Based on Variations in Age and Acoustic Impedance Contrast - Evin Yudhi Setyono Setyono; Fajar Surya Herlambang (BULETIN FISIKA, 2026)
This study investigates the characteristics of ultrasonic wave propagation in reinforced concrete at different ages and acoustic impedance contrast. Ultrasonic testing was conducted using UPV James Instrument Mark IV on non-reinforced concrete, plain-reinforced concrete, and deformed-reinforced concrete at ages of 7, 14, 28, 42, and 56 days. The analysis focused on four parameters of wave propagation, which are wave velocity, dynamic elastic modulus, acoustic impedance, and amplitude transmission coefficient. The results show that all three specimens show a similar propagation pattern. A sharp increase in velocity occurs at 7-28 days, indicating intensive hydration and microstructural densification, followed by a more gradual increase at 28-42 days. Reinforced concrete specimens steadily have higher ultrasonic velocities and acoustic impedance values than non-reinforced concrete, indicating the wave propagation path was influenced by steel reinforcement, which has a higher wave velocity and acoustic impedance than concrete. A mild reduction in velocity and acoustic impedance at 42-56 days indicates possible microstructural changes, such as moisture reduction, microcrack initiation, and increased internal scattering. The amplitude transmission coefficient was found to be slightly greater than one (T>1); this can still occur at the interface between two media with different impedances due to the transmission mechanism and normalization of wave amplitude. Steel reinforcement has a much higher acoustic impedance than concrete, so when a wave reaches the concrete-steel interface, the transmitted wave amplitude can be slightly greater than the incident wave amplitude.